2018
DOI: 10.1155/2018/1904081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aqueous Extract from Descurainia sophia (L.) Webb ex Prantl on Ventricular Remodeling in Chronic Heart Failure Rats

Abstract: Objective Descurainia sophia (L.) Webb ex Prantl (DS) is a traditional Chinese medicine. Our current study was to evaluate the effect of DS on ventricular remodeling in chronic heart failure (HF) rats and its underlying mechanism. Methods The rat chronic heart failure model induced by suprarenal abdominal aortic coarctation surgery. The survival rats were randomly divided into 3 groups: the sham group (n=6), the HF group (n=6), and the HF+DS group (n=6). After 3 months of drug intervention, we examined the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Similarly, in the rat model of myocardial ischemia, the astragalus membranaceus could enhance the myocardial cell viability via arresting the influx of Ca 2+ to prevent apoptosis [17]. The Descurainia sophia (L.) Webb ex Prantl might improve cardiac function via regulating the balance between Bax and Bcl-2, blocking the activation of Caspase3 in the chronic heart failure rats [39]. Obviously, QLC contained many antiapoptosis components.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the rat model of myocardial ischemia, the astragalus membranaceus could enhance the myocardial cell viability via arresting the influx of Ca 2+ to prevent apoptosis [17]. The Descurainia sophia (L.) Webb ex Prantl might improve cardiac function via regulating the balance between Bax and Bcl-2, blocking the activation of Caspase3 in the chronic heart failure rats [39]. Obviously, QLC contained many antiapoptosis components.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic heart failure (CHF) is the ultimate destination of most cardiovascular diseases and the leading cause of death [ 12 ]. With the development of evidence-based medicine and the deepening of basic research on heart failure, people have a deeper understanding of the pathogenesis, pathophysiological process, and clinical prevention and treatment of heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Wait for the rat to wake up from anesthesia and put it into the recovery cage (11) Rats in the sham group are operated to separate the abdominal aorta and thread, but without constriction. Suture and disinfect the incision, and then put rats into the recovery cages after anesthesia wears off (12) Postoperative analgesia in rats is very necessary. We add ibuprofen into drinking water (0.2 mg/ml) for analgesic administration (13) The survival, body weight, mental state, drinking water, diet, coat color, and activity of the rats in the two groups are closely observed and recorded after operation 2.3.…”
Section: Animal Surgerymentioning
confidence: 99%
“…[6,9,21] Gastrointestinal tract regulation effects; Bowel smooth muscle relaxation; Enhance bowel movement; Stool softener (allyl disulfide); Treatment of constipation and hemorrhoids. [9,12,[25][26][27] Cardioprotective effects; Inotropic effects (helveticoside as Na + /K + ATPase inhibitor); Diuretic effect (inhibition of renal tubular to reabsorb water, sodium, and chloride); Improve cardiac remodeling and function (activation of PI3k/Akt/mTOR dependent signaling, to attenuate cardiomyocyte apoptosis). [6,28] Anthelmintic activities; Therapeutic effects on mice infected with Himeonolepis nana.…”
Section: Referencementioning
confidence: 99%
“…Zhou et al showed that DS could decrease pleural effusion and pulmonary edema in critically ill patients [26]. Another study reported that DS could improve remodeling and cardiac function in chronic heart failure rats via attenuating cardiomyocyte apoptosis by regulating the balance between Bax and Bcl-2, blocking caspase cascades with the activation of PI3k/Akt/mTOR dependent signaling [27].…”
Section: Descurainia Sophia Activity In Cardiac Diseasesmentioning
confidence: 99%